Surveillance and identity: discourse, subjectivity and the state - Barnard-Wills, David (Ashgate, 2012)
Introduction -- Surveillance, identity, discourse and governmentality -- Discourse theory and analysis -- Representation of surveillance practices -- Subjectivity and subject positions in discourses of surveillance -- Identity in discourses of surveillance -- Conclusions and implications